Visual Popular and Political: The Non-profit Influencer and the Public Sphere - Salte, Luise (Javnost-The Public, 2022)
The influencer has become a common phenomenon in digital societies. The emphasis on exposure and popularity in social media is materialised through the growing prominence of these popular individuals with large audiences. This article examines the rhetoric of two “non-profit influencers” on Instagram, demonstrating that they can be understood beyond economics, fandom and traditional politics. Rather than being profit-focused as the more commonly known influencer, they are normatively oriented. Their communication reflects rhetorical demands prompted by the public matters they address and the social media environment. This study suggests that the non-profit influencer may be seen as a phenomenon crystallising social and technological emphases on the individual. It contends that the non-profit influencer may be located in the popular cultural public sphere, illustrating social media’s role as relevant arenas in deliberative democracy.